Effect of impact modifier to the performance of polyamide 6/high density polyethylene nanocomposite / Farizah Hamid - Hamid, Farizah (2014)
Blending of polyamide 6/high density polyethylene (PA6/HDPE=70/30 wt%) was prepared by melt compounding using a twin screw extruder followed by injection moulding. For optimum formulation, PA6/HDPE blends were blended with 1 to 5 phr of ethylene vinyl acetate (EVA) with incorporation of 3-7 wt% organoclay (MMT) and in the presence of HDPE-g-MAH (2-8 wt%) as compatibilizer. The effect of electron beam irradiation on mechanical properties of PA6/HDPE/EVA/HDPE-g- MAH/MMT nanocomposite were investigate at the dosage range of 0-200 kGy and 3.0 MeV. The mechanical properties of the samples such as tensile test, flexural test and elongation at break were measured by universal tensile machine. Hardness and impact test were measured using Zwich Roell hardness tester and Izod Impact Tester. The nanocomposites were characterized by Fourier Transform Infrared (FTIR) spectrophotometer, differential scanning calorimetry (DSC) and Thermogravimetric Analyzer (TGA). X-ray diffraction (XRD) and transmission electron microscope (TEM) were used for morphology characterization. The result revealed that incorporation of 2 wt% of HDPE-g-MAH and 5 wt% of organoclay increase the strength and stiffness of the sample but reduced the toughness property. The results exhibited enhancement of mechanical properties with incorporation of 1 phr EVA but slightly decreased for further addition of EVA content. The result shows the increasing of tensile strength and hardness at the dosage 150 kGy but slightly decline at dose up to 200 kGy. From XRD measurement, not all characteristic basal appear in the range of 20 = 2-10° which indicated that organoclay are exfoliated and intercalated during melt processing. The TEM result shows that the morphology was improved and become more homogenous after radiation. The FTIR result also shows the successful incorporation of MMT in PA6/HDPE blend and both samples with and without EVA presented almost the same trend. DSC test showed that degree of crystallinity, Xc was improved after irradiation. Meanwhile TGA test showed that both irradiated and unirradiated samples almost have same trend characterization.